(untitled) (Journal of Educational Sciences, 2019)
Researchers are considering the issues of teaching method of mathematics, in particular probability theory and statistics. Combinatorial, probabilistic, and statistical objectives have a number of features that must be taken into account in methodological planning. These tasks are distinguished from the usual school course by increased abstractness, multivariance. Increasing the level of mastering probabilistic tasks is considered using schemes and tables. A nonstandard transition from a verbal to a mathematical form of data presentation is illustrated, an attempt is made to systematize the allocation and the relationship between the original set and a number of properties of the compiled sets. The advantage of this technique is visualization, reliance on the didactic principle of visualization, which facilitates the perception of knowledge by students of the digital generation, especially in the age of visual culture. The school program in mathematics is a symbiosis of the academic and practical component of training. Today it is difficult to imagine a student’s functional literacy without the ability to perceive and analyze different forms of information, to realize the probabilistic basis of the most important patterns, and the ability to perform the necessary probabilistic analysis. A technique for presenting tasks through a visual code is proposed. Key words: visualization, «probability tree» probabilistic schemes, «classics» tables, event probability, random event.